1997
DOI: 10.1007/s004410050842
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical demonstration of Eisenia tetradecapeptide, a bioactive peptide isolated from the gut of the earthworm Eisenia foetida , in tissues of the earthworm

Abstract: The quantity and localization of Eisenia tetradecapeptide which was isolated from the gut of the earthworm Eisenia foetida were examined in tissues of the same species by enzyme-linked immunosorbent assay and immunohistochemistry. Analysis by enzyme-linked immunosorbent assay showed that Eisenia-tetradecapeptide-like immunoreactivity was present in both the central nervous system (cerebral ganglion, subesophageal ganglion, ventral ganglia, and ventral nerve cord) and the gut (esophagus, crop, gizzard, and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In a previous study, FMRFamide-IR sensory cells have also been shown to occur in Lumbricus body wall epithelium and have been clearly distinguished from pigment cells (Reglődi et al 1997a). In contrast, ETP-IR elements located in the mucosal epithelium of the gut have been described as endocrine cells (Ukena et al 1997). Few results are available concerning the occurrence of peptidergic sensory elements in invertebrates.…”
Section: Discussionmentioning
confidence: 93%
“…In a previous study, FMRFamide-IR sensory cells have also been shown to occur in Lumbricus body wall epithelium and have been clearly distinguished from pigment cells (Reglődi et al 1997a). In contrast, ETP-IR elements located in the mucosal epithelium of the gut have been described as endocrine cells (Ukena et al 1997). Few results are available concerning the occurrence of peptidergic sensory elements in invertebrates.…”
Section: Discussionmentioning
confidence: 93%
“…serotonin: Ehinger and Myhrberg 1971;Lengvári et al 1992;Rude 1969;Spörhase-Eichmann et al 1987a,b;octopamine: Csoknya et al 1996;Robertson 1975), amino acids and peptides (e.g. GABA: Telkes et al 1996; Eisenia-tetradecapeptide: Csoknya et al 2000;Ukena et al 1997;FMRFamide: Reglődi et al 1997) but some hormone-secreting cells are also known (corticotropin-releasing factor: Lubics et al 2003;gastrointestinal hormones: Reglődi et al 1999;Remy et al 1982;ACTH: Aros et al 1980;Kaloustin 1986). According to our double-staining experiments, all of the TSH-LI neurons in the CNS co-localize GABA.…”
Section: Comparison With the Distribution Of Neurotransmittersmentioning
confidence: 98%
“…This concept of braingut peptides is well known from vertebrate studies. FMRFamide, proctolin, neuropeptide Y, Eisenia tetradecapeptide, urocortin, polypeptide PACAP, cholecystokinin, gastrin, and substance P have been detected in the enteric plexus of the earthworm gut (Barna et al 2001;Ukena et al 1997;Lubics et al 2003;Somogyvari-Vigh et al 2000;Reglodi et al 1999Reglodi et al , 2000Csoknya et al 1992). …”
Section: Introductionmentioning
confidence: 96%
“…Peptides, including numerous vertebrate-like peptides, have been identified in earthworms (Sundler et al 1977;Alumets et al 1979;Aros et al 1980a,b;Ukena et al 1997;Rzasa et al 1984;Kaloustian and Edmands 1986;Lkhider et al 1987;Al-Yousuf 1990;Hasegawa and Kobayashi 1991;Lengvari et al 1994;Oumi et al 1994;Reglodi et al 1997aReglodi et al ,b, 1999Reglodi et al , 2000Somogyvari-Vigh et al 2000;Lubics et al 2003). The separate structures of the CNS and stomatogastric nervous system of earthworms have been described in detail (Friedlander 1888;Retzius 1892;Ogawa 1939;Günther 1971a,b;Schürmann and Günther 1973;Barna et al 2001).…”
Section: Introductionmentioning
confidence: 99%